An Acetate-Buffered Balanced Crystalloid Versus 0.9% Saline in Patients with End-Stage Renal Disease Undergoing Cadaveric Renal Transplantation: A Prospective Randomized Controlled Trial. (January 2015) - Potura, Eva; Lindner, Gregor; Biesenbach, Peter; Funk, Georg-Christian; Reiterer, Christian; Kabon, Barbara; Schwarz, Christoph; Druml, Wilfred; Fleischmann, Edith
Abstract : BACKGROUND: Recent studies have shown a decline in glomerular filtration rate and increased renal vasoconstriction after administration of normal saline when compared with IV solutions with less chloride. In this study, we investigated the impact of normal saline versus a chloride-reduced, acetate-buffered crystalloid on the incidence of hyperkalemia during cadaveric renal transplantation. The incidence of metabolic acidosis and kidney function were secondary aims. METHODS: In this prospective randomized controlled trial, 150 patients received normal saline or an acetate-buffered balanced crystalloid during and after cadaveric renal transplantation. Venous blood gases were obtained at the start of anesthesia and every 30 minutes until discharge from the postoperative surveillance unit. Serum creatinine and 24-hour urine output were obtained on postoperative days 1, 3, and 7. RESULTS: Patients received a similar amount of fluid (median: 2625mL [interquartile range: 2000 to 3100] vs 2500 mL [2000 to 3050], P = 0.83). Hyperkalemia, defined as serum potassium >5.9 mmol/L, occurred in 13 patients (17%) in the saline and 15 (21%) in the balanced group ( P = 0.56; difference between proportions −0.037 [−16.5% to 8.9%]). Minimum base excess was lower in the saline group compared with the balanced regimen (−4.5 mmol/L [−6 to −2.4] vs −2.6 mmol/L [−4 to −1], P < 0.001) and maximum chloride was significantly higher in the saline group (109 mmol/L [107 to 111] vs 107 mmol/L [105 to 109], P < 0.001). No difference in creatinine or urine output was seen postoperatively. Significantly more patients needed catecholamines in the saline group (30% vs 15%, P = 0.03). CONCLUSIONS: The incidence of hyperkalemia differed by less than 17% between groups. Use of balanced crystalloid resulted in less hyperchloremia and metabolic acidosis. Significantly more patients in the saline group required administration of catecholamines for circulatory support. Abstract : Published ahead of print September 3, 2014.